2022
DOI: 10.2147/ijn.s380370
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotungstate Acid Doped Polyanilines Nanorods for in situ NIR-II Photothermal Therapy of Orthotopic Hepatocellular Carcinoma in Rabbit

Abstract: Introduction Second near-infrared photothermal therapy (NIR-II PTT) has become a promising strategy for treating cancer in terms of safety and potency. However, the application of NIR-II PTT was limited in the treatment of deep-buried solid tumors due to the low dose of NIR-II absorption nanomaterials and the inadequate laser energy in the deep tumor. Methods Herein, the authors report the engineering of NIR-II absorbing polyaniline nanorods, termed HPW@PANI Nanorods, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Researchers have attempted to develop PTAs with strong absorption in the NIR II region, which has deeper tissue penetration ability than NIR I PTAs, further achieving more efficient tumor ablation. 148 Other researchers have tried irradiating tumor tissue with a fibre-optic NIR laser 149 to improve the limitation of NIR light penetration depth.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have attempted to develop PTAs with strong absorption in the NIR II region, which has deeper tissue penetration ability than NIR I PTAs, further achieving more efficient tumor ablation. 148 Other researchers have tried irradiating tumor tissue with a fibre-optic NIR laser 149 to improve the limitation of NIR light penetration depth.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol was tested for primary tumor ablation, remote tumor inhibition and the suppression of peritoneal metastasis. This experiment provides new hints for in situ NIR-II PTT implementation using optical fiber transmission of laser energy coupled with transarterial injection of NIR-II absorption nanomaterials to treat the deepest solid tumors [120].…”
Section: Investigational Studies Using Multifunctional Platforms For ...mentioning
confidence: 93%
“…Tian et al, designed and prepared NIR-II-absorbing polyaniline nanorods (HPW@PANI Nanorods) via chemical oxidative polymerization of aniline under phosphotungstic acid, which displayed successful NIR-II absorption for hyperthermia and ablation of tumoral cells [120]. The researchers applied the HPW@PANI nanorods for in situ NIR-II PTT in the orthotopic HCC in rabbits, using optical fiber transmission of laser power.…”
Section: Investigational Studies Using Multifunctional Platforms For ...mentioning
confidence: 99%
“…Moreover, due to the continuous research and development of second near-infrared (NIR-II) photothermal therapy in recent years, it has become a promising strategy for the treatment of cancer in terms of safety and efficacy. For example, in 2022, Tian et al proposed the preparation of polyaniline nanorods (HPW@PANI) by oxidative chemical polymerization of aniline with phosphotungstic acid and ammonium persulfate, which possess strong NIR-II light absorption, good photostability, enhanced photothermal conversion efficiency, and good biocompatibility and demonstrated an extremely strong inhibition of cancer cell peritoneum in a double in situ transplanted VX2 rabbit tumor model metastasis effect …”
Section: Study On the Application Of Therapeutic Nanoagents In The Tr...mentioning
confidence: 99%
“…For example, Yu et al reported in 2022 a ternary NP (HA@F-PaP/ short interfering RNA (siRNA)) synthesized by stepwise polymerization of a polyamine precursor (F-PaP) for encapsulating siRNA followed by HA encapsulation. The siRNA in the ternary NPs affects the proliferation of cancer 162 In addition to their use as carriers for chemotherapeutic drugs and RNA, organic polymer-based nanomaterials are also being developed for use as fluorescent probes in image-guided cancer surgery to achieve higher emission brightness, longer afterglow luminescence times, ideal nanoscale size and surface chemistry, imaging of tumors <1 mm, and extremely high tumor-to-normal tissue signal ratios that are currently unattainable in clinical practice. 163−165 For example, in 2018, Ni et al were the first to report near-infrared (NIR) afterglow luminescent AIE (with aggregation-induced emission properties) probes with ultralong afterglow times for facilitating image-guided cancer surgery (Figure 8a).…”
Section: Study On the Application Of Therapeutic Nanoagents In The Tr...mentioning
confidence: 99%